Pengaruh Kualitas Produk, Kemudahan, dan Kepercayaan Konsumen terhadap Keputusan Pembelian pada Lazada di Kota Batam - Febriyanti Febriyanti; Triana Ananda Rustam (Universitas Batanghari, 2023)
The e-commerce business in Indonesia has been increasing since early 2020. The development of the world of e-commerce in Indonesia is of course due to the rapid population growth to the development of the world of digital technology. purchase on Lazada in Batam City. This research uses quantitative analysis method. Data collection techniques by filling out questionnaires. This study shows that product quality, convenience, and consumer trust have a positive and significant influence on purchasing decisions at Lazada in Batam City.